Building a Repeatable Sales Processes in Early-Stage B2B Startups - Demchenko, Vasyl; Andera, Michal, 1984-; Pernica, Karel; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
The objective of the thesis is to propose an actionable guideline for early-stage founders to effectively transition from founder-led sales to consistently generating revenue sales machine. Many early-stage founders fail to achieve a product-market fit and scale the venture due to inability to design a repeatable sales model, including poor understanding of customer pain points and mastering effective distribution. The transition from opportunistic founder-led customer acquisition to consistent growth poses such challenges as choosing a growth model, defining ideal customer profile, structuring the sales funnel and scaling a sales team. The research approach applied for this research is qualitative, based on semi-structured interviews with founders and early-stage executives from early-stage B2B startups, ranging from pre-seed to series B. Data collection was performed through twelve in-depth interviews with decision-makers with field experience of implementing repeatable sales processes within early-stage startups, which allowed to gather best practices utilized by practitioners for building repeatable sales processes. The interviews were first recorded, then transcribed with the help of AI software. Next, the interviews were analysed through thematic analysis methodology to identify patterns and insights. The theoretical framework of this Thesis was built based on five key pillars: the concept of repeatable sales process, growth strategy selection methodologies, ideal customer profile development, sales team organization principles, and the implementation of AI technologies in sales operations. This study fills the gap between general sales theory and the field practices applied by the early-stage ventures. The Thesis developed step-by-step guidelines for early-stage founders and sales executives to implement repeatable sales processes, which were organized in accordance with funding stages such as Pre-seed, Seed, and Series A.
The designed guidelines will help to make reflective decisions about growth strategy selection, sales team structure, qualification frameworks, and AI implementation. The guidelines incorporate theoretical knowledge with insights derived from the interviews with practitioners, making certain they can be utilized by founders and sales executives within early-stage organisations, aiming to establish repeatable sales processes.
Vedoucí práce: Michal Andera
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses